2003
DOI: 10.1002/pola.10910
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effect on azobenzene‐based liquid‐crystalline organophosphorus polymers

Abstract: An Erratum has been published for this article in Journal of Polymer Science Part A: Polymer Chemistry (2003) 41(23) 3862A new series of combined‐type, azobenzene‐based organophosphorus liquid‐crystalline polymers were synthesized, and their photoisomerization properties were studied. The prepared polymers contained azobenzene units as both the main‐chain and side‐chain mesogens. Various groups were substituted in the terminal of the side‐chain azobenzene mesogen, and the effects of the substituents were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Phosphorous, being a non-metal overcomes this problem, when incorporated into the polymer [10][11][12]. Our earlier studies in this direction showed that the inclusion of phosphate group into the polymer backbone improved their solubility, thermal stability and char yield and reduced the glass-transition temperature (T g ) [13][14][15][16]. Literature reveals that investigation on the synthesis of photo-crosslinkable liquid crystalline polymers is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorous, being a non-metal overcomes this problem, when incorporated into the polymer [10][11][12]. Our earlier studies in this direction showed that the inclusion of phosphate group into the polymer backbone improved their solubility, thermal stability and char yield and reduced the glass-transition temperature (T g ) [13][14][15][16]. Literature reveals that investigation on the synthesis of photo-crosslinkable liquid crystalline polymers is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular weight reported in literature for main chain azo polymers generally indicates incorporation of 6-8 repeating units. 41,42 In the polymers reported here, the extent of formation of new ester linkage could be estimated based on the integration of the new ester peak at 4.48 ppm (methylene ester) from the corresponding 1 H-NMR spectra. The actual peak integration value and the percentage of new ester linkage is given in the Supporting Information Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…S4b) in purified and freeze-dried forms were measured. The characteristic peak due to the azo linkage (−N = N−) attached to tyrosine ring is identified at ~1508 cm −1 3334 and methoxy peaks are identified at 1246 and 1036 cm −1 in the methoxy-azo-M13 phage. In the case of nitro-azo-M13 phage, the azo linkage (−N = N−) identified between 1519–1479 cm −1 is found to be coupled with NO 2 stretching.…”
Section: Resultsmentioning
confidence: 99%